Endogenous 17β-estradiol regulates sexually dimorphic anxiety responses in zebrafish via the HPI axis and 5-HT/DA pathways - Hong Tao; Hong Tao; Ying–Ying Zhang; Ying–Ying Zhang; Yan–Jun Shen; Yan–Jun Shen; Qi–Liang Chen; Qi–Liang Chen; Zhi–Hao Liu; Zhi–Hao Liu (Frontiers in Marine Science)
Anxiety is a multifaceted emotional response exhibited by animals when confronted with potential threats. Among most vertebrates, including mammals and fish, there is a pronounced sexual dimorphism in anxiety responses, with females typically demonstrating higher anxiety levels than males. Concurrently, endogenous estrogen levels, specifically 17β-estradiol (E2), are significantly higher in females compared to males. This suggests a potential positive regulatory role of E2 on anxiety, contributing to sexually dimorphic anxiety in fish. To elucidate the role of E2 in mediating sexually dimorphic anxiety responses, male zebrafish (Danio rerio) were administered E2 (E2-M), while females were treated with letrozole (LET, an aromatase inhibitor that reduces E2 synthesis, LET-F) for 60 days, and plasma and brain levels of E2 were detected and anxiety response was evaluated by a novel tank diving test. Females (C-F) showed significantly higher anxiety responses, along with elevated E2 and cortisol levels in plasma and brain, and reduced brain serotonin (5-HT) and dopamine (DA) levels compared to males (C-M). Treatment with LET significantly decreased E2 levels in the plasma and brain of female zebrafish, which corresponded with reduced anxiety responses, lower plasma cortisol levels, and increased brain 5-HT and DA content. Additionally, the expression of genes associated with E2, cortisol, 5- HT, and DA pathways was relevantly altered. Conversely, E2 treatment in males (E2-M) increased E2 levels and anxiety responses, elevated plasma cortisol levels, and decreased brain 5-HT and DA content, with corresponding changes in gene expression. These findings strongly suggest that E2 positively regulates sexually dimorphic anxiety responses possibly by modulating plasma cortisol levels and the synthesis and action of 5-HT/DA in the brain.